Longitudinal Progression of Essential Tremor: Do Tremor Severity Scores Increase at a Uniform Rate? - McGurn, Margaret M.; Berry, Diane S.; Dworkin, Jordan D.; Louis, Elan D. (Frontiers in Neurology, 2022)
Background: Few longitudinal studies assess the progression of essential tremor (ET). One unexplored issue is whether tremor severity increases across time at a uniform rate. That is, does the observed rate of change in tremor severity within a particular patient remain constant or vary across time? This question of intra-individual differences is particularly important since it reflects a primary patient concern–will the nature of change I have seen to date be what I can expect in the future? Methods: ET cases were enrolled in a prospective, longitudinal study. We selected 35 cases and assessed tremor severity via Bain and Findley ratings of Archimedes spirals assigned by a senior movement disorders neurologist. After reviewing both the change in spiral scores and the rate of change in scores, we identified five mutually exclusive patterns of severity change. We calculated the prevalence of each category using two complementary sets of classification criteria. Results: Length of follow-up was 4.5 to 16.0 years, mean=10.2 years. Mean baseline tremor severity score was 4.6, SD=1.6. Depending upon the classification criteria used, the tremor scores of one-third to one-half of cases did not increase in a uniform fashion but were better described as demonstrating jumps and/or reversals in scores across time. Conclusions: We document the nature of changes in ET tremor severity scores across a ten-year period via expert ratings of Archimedes spiral drawings. Such natural history data are valuable to patients and clinicians who hope to better understand and predict the likely course of ET symptoms.